Exploring Dentistry Students' Mastery of Speaking English Using Artificial Intelligence - Atik Ulinuha; Tantry Ajeng Parnawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Mastering speaking for dentistry students is essential both for academic and professional purposes. While technology is widely integrated into the English learning process, limited study exists on the use of Artificial Intelligence (AI), in this case SmallTalk2Me, in English as a Foreign Language classroom. Thus, this study aims to elaborate on the use of AI to enhance dentistry students' speaking skills and to investigate its benefits on students' mastery of speaking English. Using the descriptive qualitative method, this study seeks a deeper understanding of students' speaking skills reflected in their interaction with the AI. 78 dentistry students were asked to do the speaking level test on SmallTalk2Me. The findings indicated that the majority of the students were in the intermediate level (30 students), followed by an upper intermediate level (27 students). In terms of speaking elements, the students demonstrated advanced proficiency in fluency (37 students) and grammar use (32 students). However, there is a need for improvement in terms of students' pronunciation (29 students) and vocabulary mastery (28 students), indicated by their intermediate level performance. The detailed as well as instant feedback provided by the AI highlights the AI's role in assisting the students in improving their speaking proficiency level. Additionally, it helps teachers in developing suitable lesson plans aligned with the student's proficiency level. In summary, this study emphasizes the benefits of integrating AI into the English and learning process, particularly for enhancing speaking skills among dentistry students.